Managing Large-Scale Deformation in Mine Tunnels in Anisotropic Rock Masses - Chapula, Brian (Curtin University, 2022)
This research investigates ways of effectively managing large-scale deformation in tunnels of underground hard rock mines. This thesis presents a method of forecasting large-scale deformation using RQD and FLAC3D. RQD and Q-system were isolated as the focal point in this research to study the likelihood of geotechnically significant deformation in underground mines. Large-scale deformation was investigated at CSA mine using FLAC3D, and the results were compared with RQD values of the area. A good correlation was found between the FLAC3D results and the RQD values.